Transformasi Tuntutan Kerja Menjadi Integrasi Kehidupan Kerja Melalui Penguatan Peran Sumber Daya Kerja - Salim, Gabriella; Zamralita, Zamralita; Purwono, Urip (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to examine the role of job resources in moderating the influence of challenge demands and hindrance demands on work-life integration. Operationally, challenge demands are defined as demands that trigger self-development, hindrance demands as obstacles to goal achievement, and job resources as physical and psychological support aspects. Work-life integration is the ability to harmoniously combine professional and personal role boundaries. The participants in the study included 223 career women working full-time as consultants in the Greater Jakarta area, married, and with children in intensive care. Data collection was done using an online questionnaire adapted from the Work-Life Integration Scale, the Job Demands Scale, and the Job Resources Scale of the JD-R model. This study used a quantitative approach with a cross-sectional design. The results of Multiple Regression analysis using PROCESS Macro Model 1 showed that challenge demands had a significant positive effect on work-life integration (B = 0.988, p < .001). A unique finding contradictory to the general literature was found for hindrance demands, which also had a significant positive effect (B = 0.457, p < .001). Moderation analysis confirmed that job resources strengthened the positive relationship for both types of demands; acting as a boosting effect for challenge demands and an enhancing effect for hindrance demands. The implications of these findings suggest that for women in consulting careers, the primary integration strategy is not to minimize the burden, but to optimize the available workforce resources to transform pressure into integration opportunities.